Weight Loss Maintenance in African American Women: A Systematic Review of the Behavioral Lifestyle Intervention Literature - Lisa M. Tussing-Humphreys; Marian L. Fitzgibbon; Angela Kong; Angela Odoms-Young (Hindawi Limited, 2013)
We performed a systematic review of the behavioral lifestyle intervention trials conducted in the United States published between 1990 and 2011 that included a maintenance phase of at least six months, to identify intervention features that promote weight loss maintenance in African American women. Seventeen studies met the inclusion criteria. Generally, African American women lost less weight during the intensive weight loss phase and maintained a lower % of their weight loss compared to Caucasian women. The majority of studies failed to describe the specific strategies used in the delivery of the maintenance intervention, adherence to those strategies, and did not incorporate a maintenance phase process evaluation making it difficult to identify intervention characteristics associated with better weight loss maintenance. However, the inclusion of cultural adaptations, particularly in studies with a mixed ethnicity/race sample, resulted in less % weight regain for African American women. Studies with a formal maintenance intervention and weight management as the primary intervention focus reported more positive weight maintenance outcomes for African American women. Nonetheless, our results present both the difficulty in weight loss and maintenance experienced by African American women in behavioral lifestyle interventions.